2007
DOI: 10.1111/j.1365-313x.2007.03398.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial demethylation of oligogalacturonides by pectin methyl esterase 1 is required for eliciting defence responses in wild strawberry (Fragaria vesca)

Abstract: SummaryIn addition to the role of the cell wall as a physical barrier against pathogens, some of its constituents, such as pectin-derived oligogalacturonides (OGA), are essential components for elicitation of defence responses. To investigate how modifications of pectin alter defence responses, we expressed the fruit-specific Fragaria · ananassa pectin methyl esterase FaPE1 in the wild strawberry Fragaria vesca. Pectin from transgenic ripe fruits differed from the wild-type with regard to the degree and patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
129
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(134 citation statements)
references
References 81 publications
(181 reference statements)
4
129
1
Order By: Relevance
“…In the strawberry-ripening process, pectin breakdown fragments of [1/4]-alinked oligogalacturonides can, potentially, be released through the action of PG or other pectinolytic enzymes. These OGAs have been demonstrated to modify gene expression and to play a role in eliciting different cellular responses as a plant-pathogen interaction in strawberry fruits (Osorio et al, 2008). However, in our case, the absence of significant transcriptomic changes in the microarray studies does not support this explanation.…”
Section: Discussioncontrasting
confidence: 56%
“…In the strawberry-ripening process, pectin breakdown fragments of [1/4]-alinked oligogalacturonides can, potentially, be released through the action of PG or other pectinolytic enzymes. These OGAs have been demonstrated to modify gene expression and to play a role in eliciting different cellular responses as a plant-pathogen interaction in strawberry fruits (Osorio et al, 2008). However, in our case, the absence of significant transcriptomic changes in the microarray studies does not support this explanation.…”
Section: Discussioncontrasting
confidence: 56%
“…Moreover, in wheat (Triticum aestivum) near-isogenic lines, a blockwise distribution of methylesters was detected in lines susceptible to Puccinia graminis compared with a more random distribution in resistant lines (Wiethölter et al, 2003). In addition, the elicitor activity of OGs is dependent on the degree and distribution of methylesters (Cabrera et al, 2008;Osorio et al, 2008). Thus, it is likely that patterns of methylesterification affect plant-pathogen interactions.…”
Section: Resultsmentioning
confidence: 99%
“…The degree and pattern of pectin methylesterification are important for pectin degradation and hence generation of OGs by pectolytic enzymes (Berger and Reid, 1979;Limberg et al, 2000aLimberg et al, , 2000b. The elicitor activity of OGs depends on their length and degree of esterification (Osorio et al, 2008;Ferrari et al, 2013). It has been shown that pectic fragments can be perceived by WALL-ASSOCIATED KINASE1 (WAK1) and WAK2 (Kohorn et al, 2009;Brutus et al, 2010).…”
mentioning
confidence: 99%
“…Besides, the induction of lipoxigenase activity demonstrated the stimulation of the octadecanoid pathaway. Moreover, transgenic strawberries (Fragaria vesca L.) producing partially demethylated OGAs displayed an enhanced resistance against Botrytis cinerea [53]. Table 1 shows that OGAs modulate diverse growth and developmental processes in plants.…”
Section: Biological Activity Pd Organism Referencementioning
confidence: 99%